Penetration of amoxycillin/clavulanic acid into bronchial mucosa with different dosing regimens. Issue 10 (October 1994) - Gould, I M; Harvey, G; Golder, D; Reid, T M; Watt, S J; Friend, J A; Legge, J S; Douglas, J G
Abstract : BACKGROUND--The efficacy of an antibiotic is related to its concentration at the site of infection. Previous studies of the concentrations of amoxycillin and clavulanic acid (co-amoxiclav) in respiratory secretions or whole lung tissue have suffered from methodological problems. The concentration of amoxycillin and clavulanic acid was determined in bronchial mucosal biopsy samples obtained at bronchoscopy following five different dosing regimens. METHODS--Bronchial biopsy and serum samples were obtained from 50 patients undergoing diagnostic bronchoscopy. Ten patients each received 375 mg, 625 mg, 750 mg, and 3.25 g oral, and 1.2 g intravenous co-amoxiclav 1-3 hours before bronchoscopy. The concentrations of clavulanic acid and amoxycillin were determined by high performance liquid chromatography using a microbore column, solid phase extraction, and preconcentration to improve sensitivity tenfold over previous methods. RESULTS--Concentrations of both clavulanic acid and amoxycillin in bronchial mucosa were dose related and were well above the MIC90 of co-amoxiclav for the common bacterial respiratory pathogens including Haemophilus influenzae, Micrococcus catarrhalis and Streptococcus pneumoniae for all dosing regimens. Mean mucosal levels were 200% and 118% of the corresponding serum levels for amoxycillin and clavulanic acid respectively. CONCLUSIONS--Amoxycillin and clavulanic acid are concentrated in bronchial mucosa and, even at the lowest dose of 375 mg orally, are likely to produce tissue levels in the lung sufficient to inhibit all the common community acquired respiratory pathogens.